GE_GERICHTE A/2770/2013 vom 30. Juni 2014 - GE Cour de justice (2014)
IMPÔT ; IMMEUBLE ; PROPRIÉTÉ FONCIÈRE ; VALEUR LOCATIVE ; VALEUR FISCALE ; IMPÔT SUR LA FORTUNE ; ESPAGNE | LIFD.6.al1; LIPP.5.al1; LIFD.7.al1; LIPP.6.al1; LHID.14.al1; LIPP.50.lete; LIFD.21.letb; LIPP.24.al1.letb